Reorientasi Ontologi, Epistemology Dan Aksiologi Dalam Perkembangan Sains - Dian Ekawati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2013)
As a perfect human being and is known as thinking beings and is known as thinking beings called homosapiens. Humans are able to maintain the existence of the earth at the same time maintaining its leadership and empower the surrounding creatures for his own benefit and using a knife scientific analysis and empirical data. Ontology is the science which deals with the nature of the existing, which is a reality in the form of the either concrete or abstract.Epistemology is the science which deals with how to gain knowledge that well known as scientific method.Three elements must be releated to each other.